THE POTENTIAL USGAE PAPER FIBER REINFORCED FOAM CONCRETE (PFRFC) WALL PANELING SYSTEM AS AN IDEA BUILDING MATERIAL - Fahrizal Zulkarnain S.T., M.Sc., Ph.D (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
One type of a new product for the usefulness of panel wall material containing mixed composite of cement, sand and recycle paper called as Paper Fiber Reinforced Foam Concrete (PFRFC) as upon of the reinforcement addition is expected can improve materials quality for non load bearing wall. Pursuant to study of paper fiber in mixture of concrete it was produce a strong structure materials, environmental friendly and economical. By that, this study have practiced using paper fiber with other mixture of lightweight foamed concrete to search out the good material for lightweight concrete in term of the tension strength, compression strength and absorption of noise. Paper fiber come from wood fiber which have experienced of crushing process, condensation, and pickling have idiosyncrasy in absorbent strength of sound and strength of tension but it is sensitive to water, slow harden and increase the density of foam concrete specimens. Experimental work of PFRFC have been conducted in the form of prism specimen, panel wall and cube, with water ratio, cement, and sand is 0.45 : 1 : 1.5 and mixed with 5%, 10%, 15% and 20% of paper fiber. The research vie shows that with addition of paper fiber, the flexural strength of the Paper Fiber Reinforced Foam Concrete (PFRFC) is increases although the compression strength of PFRFC is not as good as the flexural strength. The strength of wall panel of PFRFC is better compared to Normal Foam Concrete (NFC) wall panel in terms of the flexural strength and noise absorption. The density discovered is less than normal concrete density, which are 2400 kg/m3. The PFRFC density is appropriate for the lightweight material for wall panel, which is the range of density, are 800 - 900 kg/m3 for the specimen of PFRFC cube.